The Effect of Reducing Pain with Classic Music Therapy in Ca Mamae Patients Post-Mastectomy - Rahayu, Diah Esti; Margaretha, Sumarti Endah Purnamaningsih Maria; Sunyar, Sunyar; Yudha, Raden Rama Widya Kartika (GLOBAL HEALTH SCIENCE GROUP, 2024)
Ca Mamae or breast cancer is a malignant tumor that grows in the breast tissue, and one of the medical procedures that can be performed on Ca Mamae sufferers is mastectomy surgery. Surgical patients usually feel pain, and the therapy or action given to patients with post-operative pain to reduce pain is music therapy. Objective to describe the application of efforts to reduce pain with classical music therapy in post-operative ca mae patients in Ward Cendana 1 Dr Sardjito Hospital. The method used is a descriptive method with case studies to obtain an overview by observing and analyzing accurate data. After classical music therapy was carried out on post-operative ca mammae patients at DR Sardjito Yogyakarta Hospital with a frequency of 2-3 times a day for 3 days, the results showed that pain in post-operative ca mammae patients decreased from scale 6 (moderate pain) to scale 1 (pain light). Based on the results of a case study conducted at DR Sardjito General Hospital, Yogyakarta for 3 days with a duration of 15-20 minutes, it can be concluded that classical music therapy can reduce the pain scale in post-operative ca mamae patients.